1985
DOI: 10.1542/peds.76.5.810
|View full text |Cite
|
Sign up to set email alerts
|

Slipping Rib Syndrome: An Infrequently Recognized Entity in Children: A Report of Three Cases and Review of the Literature

Abstract: Slipping rib syndrome is a sprain disorder produced by trauma to the costal cartilages of the 8th, 9th, and 10th ribs. The symptoms are neuritic pain, autonomic symptoms, and a perception of a slipping movement of the ribs. It is frequently confused with intraabdominal disorders. Diagnosis is made by a positive hooking maneuver or demonstration of tenderness over the affected cartilages. Three case reports, a review of the literature, and a discussion of the syndrome are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The slipping rib syndrome is an underdiagnosed cause of chronic thoracic abdominal pain. [4][5][6] It was originally described as a syndrome affecting the floating ribs (one of the names used was "twelfth rib syndrome") and was typically unilateral. 7 However, several current series have found that the etiology is based on the involvement of the false ribs (8 th , 9 th , and 10 th ), with possible bilateral occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…The slipping rib syndrome is an underdiagnosed cause of chronic thoracic abdominal pain. [4][5][6] It was originally described as a syndrome affecting the floating ribs (one of the names used was "twelfth rib syndrome") and was typically unilateral. 7 However, several current series have found that the etiology is based on the involvement of the false ribs (8 th , 9 th , and 10 th ), with possible bilateral occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Often the only treatment needed is explanation, reassurance and advice on posture. Sometimes injection of local anaesthetic into the affected area is helpful, 6,7 although likely to be temporary, and there are several reports of long‐term benefit following surgical removal of the subluxing rib 8,9 …”
Section: Discussionmentioning
confidence: 99%